Effects of cigarette smoking and biomass fuel on lung function and respiratory symptoms in middle‐aged adults and the elderly in Guangdong province, China: A cross‐sectional study - Zheng, Xue‐yan; Li, Zhang‐long; Li, Chuan; Guan, Wei‐jie; Li, Li‐xia; Xu, Yan‐jun (Indoor air, 2020)
We sought to investigate the association between active cigarette smoking (ex‐ and current smokers) with or without exposure to biomass fuels and respiratory symptoms/lung function in middle‐aged adults and the elderly. In the chronic obstructive pulmonary disease surveillance conducted in six cities of Guangdong province, China, we surveyed 1986 residents aged 40‐93 years. We recorded respiratory symptoms, smoking status, use of biomass fuel, and other covariates by using a structured questionnaire. All models were adjusted for second‐hand smoking. Active smoking with or without exposure to biomass fuels was significantly associated with wheezing, chronic cough, and phlegm (all P < .05). Active smoking alone with or without exposure to biomass fuels was associated with 2.5% and 0.6% reduction in the mean forced vital capacity predicted, 6.8% and 4.2% reduction in the mean forced expiratory volume in one second predicted, and 9.0% and 4.7% reduction in the mean maximal mid‐expiratory flow predicted compared with the exposure to neither smoking nor biomass fuels, respectively. However, exposure to biomass fuel alone was associated with neither greater lung function impairment nor respiratory symptoms except for chronic cough. Efforts should be made to protect home owners and their family from adverse effects of indoor air pollution.